Impact of Blanket Configuration on the Design of a Fusion-Driven Transmutation Reactor - Bong Guen Hong (Center of Biomass & Renewable Energy, Diponegoro University, 2018)
A configuration of a fusion-driven transmutation reactor with a low aspect ratio tokamak-type neutron source was determined in a self-consistent manner by using coupled analysis of tokamak systems and neutron transport. We investigated the impact of blanket configuration on the characteristics of a fusion-driven transmutation reactor. It was shown that by merging the TRU burning blanket and tritium breeding blanket, which uses PbLi as the tritium breeding material and as coolant, effective transmutation is possible. The TRU transmutation capability can be improved with a reduced blanket thickness, and fast fluence at the first wall can be reduced. Article History: Received: July 10th 2017; Received: Dec 17th 2017; Accepted: February 2nd 2018; Available onlineHow to Cite This Article: Hong, B.G. (2018) Impact of Blanket Configuration on the Design of a Fusion-Driven Transmutation Reactor. International Journal of Renewable Energy Development, 7(1), 65-70.https://doi.org/10.14710/ijred.7.1.65-70